THE FUTURE OF SERBIAN FRUIT EXPORTS TO EGYPT: OPPORTUNITIES UNDER THE NEW FREE TRADE AGREEMENT - Stanojevic, Nataša (Economics of Agriculture, 2025)
This study examines the potential impact of the Free Trade Agreement (FTA) between Serbia and Egypt on Serbian fruit exports. It identifies fruit products with strong trade complementarity to Egypt’s import needs and projects export growth from tariff reductions. Using Revealed Comparative Advantage (RCA) and the Michaely Trade Complementarity Index (TCI), the analysis highlights Serbia’s globally competitive fruit products and their alignment with Egypt’s demand. A simulation model, incorporating Egypt’s demand elasticity and anticipated price reductions, predicts significant growth for products like fresh apples, plums, and dried apricots, while frozen fruits, despite high RCA, show limited prospects. The findings offer actionable recommendations for expanding production in high-demand sectors, leveraging Serbia’s comparative advantages, and diversifying exports to maximize FTA benefits. This study provides a strategic framework for enhancing Serbia’s fruit trade with Egypt, supporting informed policymaking and stakeholder decisions in an evolving global trade environment.